Maternal outcome amongst all deliveries of nullipara in spontaneous labor at term ≥37 weeks at a tertiary health care center in south Gujarat, India - Joshi, Manan Y.; Mistry, Urvi; Shrivastava, Anjani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Since last one decade there is rising concern over increasing rate of caesarean section in all over world, especially among nulliparous women. The national prevalence of CS in India has modestly increased over the past 25 years. According to data from the National Family Health Survey, the national CS rate in 1992-93 was 2.6% and rose to 17.2% in 2015-16. Study objective was to evaluate fetomaternal outcome of Nullipara >=37wks pregnancy in spontaneous labor. Methods: This prospective observational study was done at Obstetrics and Gynaecology Department of New Civil Hospital Surat for 6 months period after official approval from Ethical Committee. Results: In my study 65% subjects had normal vaginal delivery, 34% subjects had cesarean section and 1% had operative vaginal delivery. In comparison between total no. Of ANC visit and postpartum/intrapartum complication p-value is 0.003 which is p <0.05, which is significant, which suggests that women with 4 or less total ANC visits have higher risk of developing postpartum/intrapartum complication than women with more than 4 total ANC visits. Conclusions: The primary caesarean section among nulliparous singleton pregnancy with spontaneous labor is an important contributor to overall caesarean section of the health institute. The main indication for caesarean section were fetal distress, cephalo-pelvic disproportion and meconium stained liquor in early phase of labor. There is need to develop standard clinical protocol for management of these conditions and to promote vaginal delivery in nulliparous singleton pregnancy with spontaneous labor in eligible.